An Analysis Of Students’ Attitude In Online English Learning At Fifth Semester Of English Education Study Program In UIN Sjech M. Djamil Djambek Bukittinggi - Ratna Sari; Syahrul; Genta Sakti; Irwandi (CV. Ulil Albab Corp, 2022)
The purpose of this study was to find out the students’ attitude in Online English learning using zoom at fifth semester of English education study program in UIN Sjech M. Djamil Djambek Bukittinggi. This study used a quantitative approach with a survey design. The population of this study were the students of English education study program at fifth semester academic year 2021/2022, consisting of 127 students from 4 classes. The researcher used simple random sampling technique because the population in this study was more than one hundred so sample in this study was 25% or 32 students. In collecting the data, the researcher used an instrument in the form of a questionnaire.The results of this research related to students' attitude in online English learning using zoom at the fifth semester of English education study program in UIN Bukitinggi academic year 2021/2022 show that some of students had negative and positive attitudes. Based on the findings, the negative attitude that students generally did was turned off the zoom camera when did other activities during English class using zoom with a percentage of 100%. Sometimes most of them felt sleepy while learning English using zoom with a percentage of 90.6%. Besides, they were also had positive attitude such as they liked to speak English in English class on zoom with percentage of 62.5%. So, in general indicated that the students of English education study program at fifth semester academic year 2021/2022 in UIN Sjech M. Djamil Djambek Bukittinggi had negative attitude in learning English online using zoom.